2009
DOI: 10.1007/s10067-009-1242-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of synovial fluid leptin concentrations with the severity of osteoarthritis

Abstract: Leptin is known to play an important role in the pathophysiology of osteoarthritis (OA). This study investigated whether synovial fluid (SF) leptin level is related to the radiographic severity of OA and its role as a quantitative marker for the detection of OA. SF was obtained from 42 OA patients who underwent knee surgery and 10 who had no abnormality of articular cartilage during arthroscopic examination. The progression of OA was classified by Kellgren-Lawrence grading scale. The concentrations of leptin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
1
5

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 21 publications
8
130
1
5
Order By: Relevance
“…Leptin is considered a pro-inflammatory peptide in rheumatic diseases, whereas it is not expressed in healthy cartilage [24,25]. Indeed, recent works have shown that leptin inhibits chondrogenesis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is considered a pro-inflammatory peptide in rheumatic diseases, whereas it is not expressed in healthy cartilage [24,25]. Indeed, recent works have shown that leptin inhibits chondrogenesis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Even though plasma and/or synovial fluid levels of several cytokines and growth factors have been studied in patients with knee OA, to our knowledge, there has been no published data regarding the association of circulating and synovial fluid levels of bFGF in various clinical stages of primary knee OA [3,9,10,15,23]. Accordingly, we hypothesised that bFGF in plasma and synovial fluid could be correlated with the severity of clinical outcomes in knee OA patients.…”
Section: Introductionmentioning
confidence: 97%
“…Adiponectin stimulates PGE 2 and IL-8 production in RA synovial fibroblast (93,94). In addition, it was also reported in RA synovial fibroblast that adiponectin is able to stimulate the production of IL-6, PGE 2 , vascular endothelial growth factor, and MMP-1 and MMP-13 (43,95). In cultured chondrocytes, adiponectin also induces the production of NO, IL-6, MMP-3, MMP-9, and monocyte chemotactic protein 1 (MCP-1) (96).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 77%
“…It is known that leptin expression is much higher in human OA cartilage than in normal cartilage. Moreover, leptin expression in chondrocytes, as in synovial fluid, correlates with the severity of the disease (42)(43)(44). Considering the sexual dimorphism of leptin circulating levels, it has been hypothesized that the increased predisposition of women to develop OA could be due to the higher circulating levels observed in women in comparison with men (45).…”
Section: Adipokines In Rheumatic Diseases and Cardiovascular Complicamentioning
confidence: 99%